Low-cost high-performance full-biodegradable polylactic acid-based heat-shrinkable film and preparation method thereof

By using a composite system of PLA and PBAT in the heat-shrinked film materials, combined with multi-component epoxy chain extenders, inorganic nanofillers and ultraviolet cross-linking additives, the problem that existing heat-shrinked film materials is difficult to achieve low cost, total biodegradation and high heat-shrinkage performance, and an efficient and environmentally friendly heat-shrinkage preparation is achieved.

CN119570208APending Publication Date: 2025-03-07HE NAN NAI KE DA CAI SE YIN SHUA YOU XIAN GONG SI

Patent Information

Application Number
CN202411667362.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing heat-shrinking film materials are difficult to achieve both low cost, full biodegradation and high heat-shrinking properties, and the recycling cost is high, making it difficult to truly degrade, resulting in environmental pollution.

Method used

Polylactic acid (PLA) and polyterephthalic acid-butadiene adipicate (PBAT) are used as the main raw materials, combined with multi-component epoxy chain extenders, inorganic nanofillers and ultraviolet cross-linking additives, and low-cost and high-performance fully biodegradable polylactic acid-based heat shrink films are prepared through reasonable proportioning and processing technology.

Benefits of technology

The low cost, high performance and full biodegradation of polylactic acid-based heat shrink films are achieved, reducing the "white pollution" of plastics, and improving the mechanical properties, heat shrinkage properties and shape memory properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570208A_ABST
    Figure CN119570208A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost high-performance full-biodegradable polylactic acid-based heat-shrinkable film which is prepared from the following raw materials in parts by weight: 10-30 parts of polylactic resin, 70-90 parts of poly (butylene adipate-co-terephthalate) resin, 0.5-5 parts of a chain extension compatibilizer, 0.1-1 part of an antioxidant, 1-3 parts of a lubricant, 5-30 parts of a modified inorganic filler and 1-5 parts of an ultraviolet radiation aid, the invention also discloses a preparation method of the thermal shrinkage film. According to the thermal shrinkage film, the plastic component can be completely biodegraded in the natural environment, serious white pollution caused by the fact that the plastic is discarded into the natural environment is avoided, meanwhile, the lactide raw material part for synthesizing the PLA resin comes from grain processing by-products, and value-added utilization of the grain processing by-products is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmentally friendly functional polymer films, and specifically relates to a low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film and a preparation method thereof. Background Art

[0002] Heat shrink film has shape memory function, can shrink when heated, and plays the role of stabilizing, covering and protecting products. At present, heat shrink film is mainly used in plastic packaging in the fields of food, medicine, electronic components, large machinery and equipment, communication equipment, etc. Its market growth rate is amazing and has become a hot spot in the plastic packaging industry. Common heat shrink films on the market mainly include polyvinyl chloride (PVC) film, polyethylene (PE) film, polypropylene (PP) film, polyethylene terephthalate (PET) film, uniaxially oriented polystyrene (OPS) film, polyvinylidene chloride (PVDC) film, polyolefin multilayer co-extruded heat shrink film (POF) and cross-linked film, among which BOPET, POF and cross-linked film have become heat shrink film materials fully promoted by Western developed countries because of their environmental protection and excellent performance, and their development is also actively promoted in China. However, most heat shrink film materials have high recycling costs and are difficult to truly degrade. Abandoning them in the natural environment will cause serious "white pollution", and the plastic particles produced by decomposition will also have a profound and adverse impact on the environment and human body. Therefore, it is urgent to develop low-cost fully biodegradable heat shrink film.

[0003] Polylactic acid (PLA) has two major characteristics: "biodegradable" and "plant-derived", and has good mechanical and processing properties. It is a biodegradable plastic with broad application prospects. However, PLA as a heat shrink film material also has the following shortcomings: 1. PLA is hard and brittle, has low impact resistance, and low comprehensive mechanical properties; low melt strength, poor thermal stability, easy high temperature degradation, and poor processing performance; 2. PLA is a semi-crystalline polymer with poor shape memory properties; 3. The energy consumption in the PLA polymerization process and the cost of lactide make the production cost of PLA higher than that of traditional heat shrink polymer materials.

[0004] Polybutylene terephthalate-adipate (PBAT) has good toughness and is complementary to PLA in terms of performance. PBAT has a high degree of industrialization and its cost is close to that of traditional general-purpose plastics, which has greater practical value in production practice. However, PLA and PBAT have poor compatibility, have a phase separation structure after compounding, and have low mechanical properties, so they need to be modified by volume expansion. There are many volume expansion modifiers for PLA and PBAT, among which the polycyclic epoxy chain extender contains epoxy groups, which can react with the end groups of PLA and PBAT, and can not only play a role in volume expansion, but also have the effect of chain extension. Therefore, the introduction of polycyclic epoxy chain extenders can improve the mechanical properties and processing properties of the system at the same time; at the same time, the introduction of inorganic nanofillers can not only reduce material costs, but also improve the two-phase distribution of PLA and PBAT, promote the melt crystallization of PLA and PBAT, and improve mechanical properties while reducing costs; the introduction of ultraviolet light cross-linking aids can introduce cross-linking structures into the system under ultraviolet irradiation, regulate the microscopic phase structure of the PLA / PBAT system, and improve shape memory properties.

[0005] Liu Xiaohua et al. (Liu Xiaohua. Research on the Radiation Effect and Thermal Shrinkage Performance of PBAT / PLA Blend Film [D]. Henan University of Technology, 2022.) studied the thermal shrinkage properties of the PLA / PBAT / thermoplastic starch system, and introduced a cross-linked structure into the system by γ-ray irradiation. The prepared heat-shrinkable composite film has excellent thermal shrinkage properties, but the composite film has poor water resistance and durability, and the cost of γ-ray irradiation is relatively high; the Chinese invention patent with patent number CN202110720931.9 discloses a high-barrier biodegradable composite film and its preparation process. The patent adopts a PLA / PBAT system through The formula is adjusted reasonably to prepare a three-layer composite film structure. The final three-layer composite film structure has the advantages of fast degradation speed, good barrier properties, high surface tension, and good printing adaptability, but does not have heat shrinkage performance; in addition, the Chinese invention patent with patent number 202311206699.2 discloses a modified masterbatch of a fully biodegradable heat shrinkable film and a preparation method thereof. The patent uses PLA as a matrix and adds plasticizers, chain extenders, etc. to prepare a modified masterbatch of a heat shrinkable film. The preparation process is simple and the material is fully biodegradable, but the amount of PLA used is large (64 parts) and the heat shrinkage temperature of the heat shrinkable film is high, which makes the product cost high and difficult to apply in the market.

[0006] Although the above PLA-based films have good performance, they cannot achieve the goals of low cost, high performance, full biodegradability, and high heat shrink performance at the same time. So far, there is still a lack of mature polylactic acid-based heat shrinkable film products on the market. Summary of the invention

[0007] The purpose of the present invention is to provide a low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film, and at the same time provide a method for preparing the film, so as to realize the industrialization of polylactic acid-based biodegradable heat shrinkable film and reduce plastic "white pollution".

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A low-cost, high-performance, fully biodegradable polylactic acid-based heat-shrinkable film is prepared from the following raw materials in parts by weight: 10 to 30 parts of polylactic acid resin, 70 to 90 parts of polybutylene terephthalate-adipate resin, 0.5 to 5 parts of chain extender and compatibilizer, 0.1 to 1 part of antioxidant, 1 to 3 parts of lubricant, 5 to 30 parts of modified inorganic filler and 1 to 5 parts of ultraviolet radiation auxiliary agent.

[0010] Preferably, a low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is made of the following raw materials in parts by weight: 15 to 25 parts of polylactic acid resin, 80 to 90 parts of polybutylene terephthalate-adipate resin, 0.5 to 3 parts of chain extender and compatibilizer, 0.1 to 1 part of antioxidant, 1 to 3 parts of lubricant, 8 to 25 parts of modified inorganic filler, and 1 to 5 parts of ultraviolet radiation additive.

[0011] Preferably, the compatibilizer and chain extender is one or two of ADR4370S, ADR4370F, ADR4368, ADR4468, ADR4400, and SG-20.

[0012] Preferably, the antioxidant is at least one of phenolic antioxidants, vitamin E, thioester antioxidants, and phosphite antioxidants.

[0013] Preferably, the lubricant is one of stearic acid lubricants, acrylate lubricants, polyethylene wax powder, and silicone.

[0014] Preferably, the modified filler is at least one of nano calcium carbonate, nano silicon dioxide, organic modified montmorillonite, talc, diatomaceous earth, nano hydroxyapatite (n-HA), and microcrystalline cellulose, and the filler size is 100 nm to 50 μm.

[0015] Preferably, the ultraviolet radiation auxiliary agent is one or two of benzophenone, methyl benzoylformate, alkyl phenones, triallyl isocyanurate, benzoin dimethyl ether, 1-hydroxycyclohexyl phenyl ketone, and benzil.

[0016] The method for preparing the above-mentioned low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film comprises the following steps:

[0017] S1. Raw material processing and extrusion: The raw materials are transported from the storage bin to the mixing hopper through the feeding system according to the proportion. The materials are preliminarily premixed in the mixing hopper, premixed evenly and processed by filtering and metal separator to filter out large impurities and entrained metal debris, and then enter the extruder. Under the heating and shearing action of the twin-screw extruder, the materials are melted and plasticized evenly, and extruded through the die under the conveying action of the screw to obtain a heat shrinkable film sheet, wherein the premixing speed is 250-400rpm, and the premixing time is 3-5min; the extrusion section temperature of the extruder is 170-190°C, the die temperature is 200-220°C, and the twin-screw speed is 60-100rpm; the thickness of the extruded sheet of the extruder is 300-800μm;

[0018] S2, film blowing: The plasticized heat shrinkable film sheet is shaped by the expansion, stretching and cooling of the compressed air at the die. The thickness of the heat shrinkable film is controlled by the air pressure. At the same time, attention should be paid to the coordination of the extrusion rate and the film blowing stretching rate to ensure that the heat shrinkable film product is fully formed and has uniform thickness, and finally a heat shrinkable film semi-finished product is obtained; the compressed air pressure in the film blowing section is 0.6-0.8MPa; the film stretching rate is set to 150-300mm / min;

[0019] S3, irradiation crosslinking: the semi-finished heat shrinkable film formed by expansion and stretching is irradiated and crosslinked by a UV curing machine to obtain a heat shrinkable film; wherein the power of the UV curing machine is 80-120W / cm; the film passing rate is set to 150-300mm / min; the wavelength range of the ultraviolet light used is 300-450nm; this step introduces a crosslinking structure into the molecular chain of the heat shrinkable film through short-term ultraviolet irradiation to improve the mechanical properties and heat shrinkage properties of the PLA-based heat shrinkable film;

[0020] S4, slitting and packaging: After UV irradiation and qualified testing, the heat shrinkable film is first trimmed on both sides by a trimmer, then rolled into bundles on a winder, and cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0021] Preferably, the thickness of the heat shrinkable film in S3 is 20-30 μm.

[0022] The principle of the present invention is: by rationally constructing a composite system, taking biodegradable and renewable PLA resin as a matrix, selecting PBAT with low cost and high toughness and complementary performance to toughen and modify PLA, considering that PLA and PBAT have poor compatibility and obvious phase separation, selecting and introducing a multi-epoxy chain extender that can chemically react with the end groups of PLA and PBAT respectively, increasing the capacity of the PBAT / PLA system and extending the chain of PLA, thereby improving the mechanical properties and melt strength of the material; at the same time, regulating the microphase structure of the system, introducing nanofillers, adjusting the crystallinity and crystal size of PBAT, and introducing a cross-linking structure, thereby improving the mechanical properties and deformation recovery ability of the material, reducing the deformation temperature, and improving the heat shrinkage performance.

[0023] The present invention has the following advantages and beneficial results:

[0024] The PLA-based heat shrinkable film prepared by the present invention has plastic components that can be completely biodegraded in the natural environment, thereby avoiding serious "white pollution" caused by discarding plastics into the natural environment. At the same time, part of the lactide raw material for synthesizing the PLA resin comes from food processing by-products, which is conducive to the value-added utilization of food processing by-products and complies with the national strategic development plan for environmental protection and energy conservation.

[0025] The PLA-based heat shrinkable film prepared by the present invention has the most expensive raw material PLA resin accounting for less than 15% (mass ratio), the largest component PBAT resin has a high degree of industrialization and its cost is slightly higher than that of traditional general-purpose plastics, and the added inorganic filler is also very cheap, so the overall material cost of the film is less than 13,000 yuan / ton, and the product has industrialization prospects.

[0026] The PLA-based heat shrinkable film prepared by the present invention has excellent shape memory performance of the material through the optimized design of the system and the reasonable regulation of the structure, wherein the film shape fixation rate is greater than 99%, the shape recovery rate is greater than 95%, and the deformation temperature is close to 60°C; at the same time, the mechanical properties are good, the maximum tensile strength is greater than 30MPa, the elongation at break is greater than 400%, and the processing performance is also good.

[0027] The PLA-based heat shrinkable film prepared by the present invention adopts an organically modified nanofiller as a modifier and introduces a three-dimensional cross-linked structure, so that the material has excellent water resistance and water vapor isolation performance, the water vapor permeability coefficient is ≤1.0×10-12g / (cm·s·Pa), and the oxygen permeability is ≤2.0×10-5g / (m2·d·Pa). The shelf life of the heat shrinkable film can be effectively extended and the use scenarios can be expanded, such as being used as a degradable packaging for food and medicine.

[0028] At the same time, the processing method and equipment adopted by the present invention are all general plastic processing equipment, one-step molding, simple and easy to operate production process, which also helps to reduce production costs and improve product benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a flow chart for preparing the low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.

[0031] In the following examples, the size of the modified inorganic filler is 100nm to 50μm,

[0032] Comparative Example 1

[0033] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 0.5 parts of compatibilizer ADR4468, 0 parts of organic modified montmorillonite, 0 parts of benzophenone BP, 0 parts of triallyl isocyanurate (TAIC), 0.5 parts of antioxidant 1010, and 1 part of lubricant stearic acid.

[0034] The above-mentioned materials are prepared through the following processing flow. After the materials are dried, they are transported from the storage bin to the mixing hopper through the feeding system according to the dosage. The materials are preliminarily mixed in the mixing hopper, the premixing speed is 300rpm, and the premixing time is 3min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170℃~190℃, the screw speed is 80rpm, the temperature at the die is 210℃, and the thickness of the die extruded sheet is about 0.8mm; the die extruded sheet is shaped by the biaxial stretching and cooling action of compressed air, the compressed air pressure is 0.8MPa, and the film thickness is 25~30μm; the film is temporarily not irradiated and cross-linked in the ultraviolet curing section, and the heat shrinkable film that has passed the inspection is trimmed and rolled by a trimming machine, and then the heat shrinkable film is cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0035] Comparative Example 2

[0036] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 0.75 parts of compatibilizer ADR4468, 0 parts of organic modified montmorillonite, 0 parts of benzophenone BP, 0 parts of triallyl isocyanurate (TAIC), 0.5 parts of antioxidant 1010, and 1 part of lubricant stearic acid.

[0037] The above-mentioned materials are prepared through the following processing flow. After the materials are dried, they are transported from the storage bin to the mixing hopper through the feeding system according to the dosage. The materials are preliminarily mixed in the mixing hopper, the premixing speed is 300rpm, and the premixing time is 3min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170℃~190℃, the screw speed is 80rpm, the temperature at the die is 210℃, and the thickness of the die extruded sheet is about 0.8mm; the die extruded sheet is shaped by the biaxial stretching and cooling action of compressed air, the compressed air pressure is 0.8MPa, and the film thickness is 25~30μm; the film is temporarily not irradiated and cross-linked in the ultraviolet curing section, and the heat shrinkable film that has passed the inspection is trimmed and rolled by a trimming machine, and then the heat shrinkable film is cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0038] Comparative Example 3

[0039] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 1.0 parts of a compatibilizer ADR4468, 0 parts of organic modified montmorillonite, 0 parts of benzophenone BP, 0 parts of triallyl isocyanurate (TAIC), 0.5 parts of an antioxidant 1010, and 1 part of a lubricant stearic acid.

[0040] The above-mentioned materials are prepared through the following processing flow. After the materials are dried, they are transported from the storage bin to the mixing hopper through the feeding system according to the dosage. The materials are preliminarily mixed in the mixing hopper, the premixing speed is 300rpm, and the premixing time is 3min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170℃~190℃, the screw speed is 80rpm, the temperature at the die is 210℃, and the thickness of the die extruded sheet is about 0.8mm; the die extruded sheet is shaped by the biaxial stretching and cooling action of compressed air, the compressed air pressure is 0.8MPa, and the film thickness is 25~30μm; the film is temporarily not irradiated and cross-linked in the ultraviolet curing section, and the heat shrinkable film that has passed the inspection is trimmed and rolled by a trimming machine, and then the heat shrinkable film is cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0041] Table 1. Related properties of the heat shrinkable films prepared in the above comparative examples 1-3

[0042] project Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength / MPa 19.8 24.6 27.3 Elongation at break / % 563.4 532.4 486.9 Shape recovery rate / % 86.7 91.6 89.3 Melt index / g / 10min 30.3 25.6 22.5

[0043] The processing technology and other formula ratios are fixed, and only the amount of the compatibilizer / chain extender ADR4468 in the formula is changed. From the data of Table 1 Comparative Examples 1-3, it can be found that as the amount of the compatibilizer / chain extender increases, the tensile strength gradually increases and the elongation at break gradually decreases. The reason is that as the amount of ADR4468 added increases, ADR4468 can react with the PLA and PBAT molecular chains, the adhesion of the PLA / PBAT two-phase interface is enhanced, the phase interface becomes blurred, and the interface effect is improved; at the same time, due to the lengthening of the molecular chain, the melt viscosity increases, the melt index decreases, and the melt strength is enhanced; the shape recovery rate shows a trend of first increasing and then decreasing. The reason for the increase is the increase in the fixed phase caused by slight cross-linking, and the reason for the decrease is the decrease in PLA crystallinity.

[0044] Comparative Example 4

[0045] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 0.75 parts of compatibilizer ADR4468, 5 parts of organic modified montmorillonite, 0 parts of benzophenone BP, 0 parts of triallyl isocyanurate (TAIC), 0.5 parts of antioxidant 1010, and 1 part of lubricant stearic acid.

[0046] The above-mentioned materials are prepared through the following processing flow. After the materials are dried, they are transported from the storage bin to the mixing hopper through the feeding system according to the dosage. The materials are preliminarily mixed in the mixing hopper, the premixing speed is 300rpm, and the premixing time is 3min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170℃~190℃, the screw speed is 80rpm, the temperature at the die is 210℃, and the thickness of the die extruded sheet is about 0.8mm; the die extruded sheet is shaped by the biaxial stretching and cooling action of compressed air, the compressed air pressure is 0.8MPa, and the film thickness is 25~30μm; the film is temporarily not irradiated and cross-linked in the ultraviolet curing section, and the heat shrinkable film that has passed the inspection is trimmed and rolled by a trimming machine, and then the heat shrinkable film is cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0047] Comparative Example 5

[0048] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 0.75 parts of a compatibilizer ADR4468, 10 parts of organic modified montmorillonite, 0 parts of benzophenone BP, 0 parts of triallyl isocyanurate (TAIC), 0.5 parts of an antioxidant 1010, and 1 part of a lubricant stearic acid.

[0049] The above-mentioned materials are prepared through the following processing flow. After the materials are dried, they are transported from the storage bin to the mixing hopper through the feeding system according to the dosage. The materials are preliminarily mixed in the mixing hopper, the premixing speed is 300rpm, and the premixing time is 3min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170℃~190℃, the screw speed is 80rpm, the temperature at the die is 210℃, and the thickness of the die extruded sheet is about 0.8mm; the die extruded sheet is shaped by the biaxial stretching and cooling action of compressed air, the compressed air pressure is 0.8MPa, and the film thickness is 25~30μm; the film is temporarily not irradiated and cross-linked in the ultraviolet curing section, and the heat shrinkable film that has passed the inspection is trimmed and rolled by a trimming machine, and then the heat shrinkable film is cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0050] Comparative Example 6

[0051] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 0.75 parts of a compatibilizer ADR4468, 15 parts of organic modified montmorillonite, 0 parts of benzophenone BP, 0 parts of triallyl isocyanurate (TAIC), 0.5 parts of an antioxidant 1010, and 1 part of a lubricant stearic acid.

[0052] The above-mentioned materials are prepared through the following processing flow. After the materials are dried, they are transported from the storage bin to the mixing hopper through the feeding system according to the dosage. The materials are preliminarily mixed in the mixing hopper, the premixing speed is 300rpm, and the premixing time is 3min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170℃~190℃, the screw speed is 80rpm, the temperature at the die is 210℃, and the thickness of the die extruded sheet is about 0.8mm; the die extruded sheet is shaped by the biaxial stretching and cooling action of compressed air, the compressed air pressure is 0.8MPa, and the film thickness is 25~30μm; the film is temporarily not irradiated and cross-linked in the ultraviolet curing section, and the heat shrinkable film that has passed the inspection is trimmed and rolled by a trimming machine, and then the heat shrinkable film is cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0053] Table 2 Related properties of the heat shrinkable films prepared in Comparative Examples 2, 4-6

[0054]

[0055]

[0056] The processing technology and basic material formula are fixed, and only the amount of modified filler in the formula is changed. The mechanical properties of the polylactic acid-based heat shrinkable material are shown in Table 2. From the data in the table, it can be found that with the increase in the amount of modified organic montmorillonite (OMMT), the tensile strength, elongation at break, impact strength, and shape recovery rate of the material all show a trend of first increasing and then decreasing. When the amount of OMMT is 10 parts, the material performance is the best. The reason may be that with the increase in the amount of OMMT, the crystallinity of PLA and PBAT increases, and OMMT can also play a role in improving the phase distribution of the two, so the mechanical properties and shape memory properties of the material increase; but with the increase in the amount of OMMT, OMMT is difficult to disperse evenly in the resin matrix, and agglomeration occurs, so the material performance does not increase but decreases.

[0057] Example 1

[0058] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 0.75 parts of a compatibilizer ADR4468, 10 parts of organic modified montmorillonite, 1.0 parts of benzophenone BP, 0.5 parts of triallyl isocyanurate (TAIC), 0.5 parts of an antioxidant 1010, and 1 part of a lubricant stearic acid.

[0059] The above materials are prepared by the following processing flow: after drying, the materials are transported from the storage bin to the mixing hopper through the feeding system according to the dosage; the materials are preliminarily mixed in the mixing hopper, the premixing speed is 300 rpm, and the premixing time is 3 min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170°C to 190°C, the screw speed is 80 rpm, the temperature at the die is 210°C, and the die extruded sheet thickness is about 0.8 mm; the die extruded sheet is shaped by the biaxial stretching and cooling of compressed air, and under the traction effect It is transported forward to the UV curing section, with a compressed air pressure of 0.8MPa and a film thickness of 25-30μm; the film is irradiated and cross-linked in the UV curing section, and the irradiation dose is adjusted by the pulling rate and irradiation power, and the power of the UV curing instrument is set to 100W / cm; the film passing rate is set to 150mm / min; the heat shrinkable film that has been UV irradiated and tested and qualified is trimmed and rolled up by a trimming machine, and then cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0060] Example 2

[0061] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 0.75 parts of a compatibilizer ADR4468, 10 parts of organic modified montmorillonite, 1.0 parts of benzophenone BP, 1.0 parts of triallyl isocyanurate (TAIC), 0.5 parts of an antioxidant 1010, and 1 part of a lubricant stearic acid.

[0062] The above materials are prepared by the following processing flow: after drying, the materials are transported from the storage bin to the mixing hopper through the feeding system according to the dosage; the materials are preliminarily mixed in the mixing hopper, the premixing speed is 300 rpm, and the premixing time is 3 min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170°C to 190°C, the screw speed is 80 rpm, the temperature at the die is 210°C, and the die extruded sheet thickness is about 0.8 mm; the die extruded sheet is shaped by the biaxial stretching and cooling of compressed air, and under the traction effect It is transported forward to the UV curing section, with a compressed air pressure of 0.8MPa and a film thickness of 25-30μm; the film is irradiated and cross-linked in the UV curing section, and the irradiation dose is adjusted by the pulling rate and irradiation power, and the power of the UV curing instrument is set to 100W / cm; the film passing rate is set to 150mm / min; the heat shrinkable film that has been UV irradiated and tested and qualified is trimmed and rolled up by a trimming machine, and then cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0063] Example 3

[0064] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 12 parts of polylactic acid, 88 parts of PBAT plastic, 0.75 parts of a compatibilizer ADR4468, 10 parts of organic modified montmorillonite, 1.0 parts of benzophenone BP, 1.5 parts of triallyl isocyanurate (TAIC), 0.5 parts of an antioxidant 1010, and 1 part of a lubricant stearic acid.

[0065] The above materials are prepared by the following processing flow: after drying, the materials are transported from the storage bin to the mixing hopper through the feeding system according to the dosage; the materials are preliminarily mixed in the mixing hopper, the premixing speed is 300 rpm, and the premixing time is 3 min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170°C to 190°C, the screw speed is 80 rpm, the temperature at the die is 210°C, and the die extruded sheet thickness is about 0.8 mm; the die extruded sheet is shaped by the biaxial stretching and cooling of compressed air, and under the traction effect It is transported forward to the UV curing section, with a compressed air pressure of 0.8MPa and a film thickness of 25-30μm; the film is irradiated and cross-linked in the UV curing section, and the irradiation dose is adjusted by the pulling rate and irradiation power, and the power of the UV curing instrument is set to 100W / cm; the film passing rate is set to 150mm / min; the heat shrinkable film that has been UV irradiated and tested and qualified is trimmed and rolled up by a trimming machine, and then cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0066] Table 3 Related properties of the heat shrinkable films prepared in Comparative Example 5 and Examples 1-3

[0067]

[0068] The processing technology and other formula ratios are fixed, and only the amount of TAIC in the UV light initiator is changed. The properties of the polylactic acid-based heat shrinkable film are shown in Table 3. From the data in the figure, it can be observed that with the increase in the amount of TAIC, the chain extension effect of the material is significant, and the elongation at break and the melt index of the material drop sharply when a partial cross-linking structure is introduced; due to the increase in the fixed phase, the shape memory property of the material is improved, but when the cross-linking is too high, the material becomes brittle, and the crystallinity of PLA decreases, so the tensile strength and heat shrinkage performance deteriorate, and there is an optimal value for the amount of cross-linking agent.

[0069] Example 4

[0070] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 10 parts of polylactic acid, 70 parts of PBAT plastic, 0.5 parts of a compatibilizer ADR4368, 2 parts of nano-calcium carbonate, 3 parts of nano-silicon dioxide, 0.1 parts of vitamin E, 3 parts of lubricant acetone, and 2 parts of methyl benzoylformate.

[0071] The above materials are prepared by the following processing flow: after drying, the materials are transported from the storage bin to the mixing hopper through the feeding system according to the dosage; the materials are preliminarily mixed in the mixing hopper, the premixing speed is 250rpm, and the premixing time is 3min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170℃~180℃, the screw speed is 60rpm, the temperature at the die is 200℃, and the thickness of the die extruded sheet is about 0.3mm; the die extruded sheet is shaped by the biaxial stretching and cooling of compressed air, and then traction is applied to the sheet. The film is transported down and forward to the UV curing section, with a compressed air pressure of 0.6MPa and a film thickness of 20-25μm; the film is irradiated and cross-linked in the UV curing section, and the irradiation dose is adjusted by the pulling rate and irradiation power, and the power of the UV curing instrument is set to 80W / cm; the film passing rate is set to 200mm / min; the heat shrinkable film that has been UV irradiated and tested and qualified is trimmed and rolled up by a trimming machine, and then cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0072] Example 5

[0073] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 30 parts of polylactic acid, 80 parts of PBAT plastic, 1 part of compatibilizer ADR4370F, 2 parts of compatibilizer ADR4370S, 10 parts of diatomaceous earth, 20 parts of nano-hydroxyapatite (n-HA), 0.1 part of vitamin E, 0.9 part of thiodipropionate, 1 part of lubricant polyethylene wax powder, and 1 part of benzoin dimethyl ether.

[0074] The above materials are prepared by the following processing flow: after drying, the materials are transported from the storage bin to the mixing hopper through the feeding system according to the dosage; the materials are preliminarily mixed in the mixing hopper, the premixing speed is 400 rpm, and the premixing time is 5 min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 180°C to 190°C, the screw speed is 100 rpm, the temperature at the die is 220°C, and the die extruded sheet thickness is about 0.5 mm; the die extruded sheet is shaped by the biaxial stretching and cooling of compressed air, and then traction is applied to the extruder section. The film is transported forward to the UV curing section, with a compressed air pressure of 0.7MPa and a film thickness of 20-30μm; the film is irradiated and cross-linked in the UV curing section, and the irradiation dose is adjusted by the pulling rate and irradiation power, and the power of the UV curing instrument is set to 120W / cm; the film passing rate is set to 180mm / min; the heat shrinkable film that has been UV irradiated and tested and qualified is trimmed and rolled up by a trimming machine, and then cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0075] Example 6

[0076] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 15 parts of polylactic acid, 90 parts of PBAT plastic, 1 part of compatibilizer ADR4400, 15 parts of organic modified montmorillonite, 10 parts of talc, 0.7 parts of phosphite antioxidant, 2 parts of lubricant acrylate, 2 parts of 1-hydroxycyclohexyl phenyl ketone, and 3 parts of alkyl phenone.

[0077] The above materials are prepared by the following processing flow: after drying, the materials are transported from the storage bin to the mixing hopper through the feeding system according to the dosage; the materials are preliminarily mixed in the mixing hopper, the premixing speed is 350rpm, and the premixing time is 4min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 175℃~185℃, the screw speed is 90rpm, the temperature at the die is 210℃, and the die extruded sheet thickness is about 0.6mm; the die extruded sheet is shaped by the biaxial stretching and cooling of compressed air, and under the traction action It is transported forward to the UV curing section, with a compressed air pressure of 0.8MPa and a film thickness of 25-30μm. The film is irradiated and cross-linked in the UV curing section, and the irradiation dose is adjusted by the pulling rate and irradiation power. The power of the UV curing instrument is set to 110W / cm2. The film passing rate is set to 220mm / min. The heat shrinkable film that has been UV irradiated and tested and qualified is trimmed and rolled up by a trimming machine, and then cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0078] Example 7

[0079] A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film is prepared from the following raw materials in parts by weight: 25 parts of polylactic acid, 75 parts of PBAT plastic, 82 parts of a compatibilizer ADR436, 8 parts of nano-calcium carbonate, 0.3 parts of vitamin E, 1 part of a lubricant acetone, and 3 parts of methyl benzoylformate.

[0080] The above materials are prepared by the following processing flow: after drying, the materials are transported from the storage bin to the mixing hopper through the feeding system according to the dosage, and the materials are preliminarily mixed in the mixing hopper, the premixing speed is 280rpm, and the premixing time is 3min; then the materials are melted and plasticized in the extruder section, the extruder temperature range is 170℃~190℃, the screw speed is 70rpm, the temperature at the die is 210℃, and the thickness of the die extruded sheet is about 0.7mm; the die extruded sheet is shaped by the biaxial stretching and cooling of compressed air, and then traction is applied to the extruder section. The film is transported forward to the UV curing section, with a compressed air pressure of 0.7MPa and a film thickness of 25-30μm; the film is irradiated and cross-linked in the UV curing section, and the irradiation dose is adjusted by the pulling rate and irradiation power, and the power of the UV curing instrument is set to 90W / cm; the film passing rate is set to 270mm / min; the heat shrinkable film that has been UV irradiated and tested and qualified is trimmed and rolled up by a trimming machine, and then cut into the specifications required by the user by a slitting machine, and finally packaged to obtain the final heat shrinkable film product.

[0081] Table 4 Relevant properties of the heat shrinkable films prepared in Examples 4-7

[0082]

[0083] In summary, the polylactic acid-based heat-shrinkable film of the present invention is a PLA-based heat-shrinkable film prepared through reasonable material optimization and structural design. The heat-shrinkable film is not only biodegradable, but also has excellent mechanical properties and heat shrinkage properties. At the same time, the material cost is controllable, which is conducive to the industrialization and promotion of PLA-based heat-shrinkable films.

[0084] The above examples are implementation methods of part of the present invention, but the implementation methods of the present invention are not limited to the above implementation cases. Any other changes, substitutions, modifications, combinations, and simplifications that do not deviate from the spirit and design principles of the present invention should be regarded as equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film, characterized in that: The invention is prepared from the following raw materials in parts by weight: 10 to 30 parts of polylactic acid resin, 70 to 90 parts of polybutylene terephthalate-adipate resin, 0.5 to 5 parts of chain extender and compatibilizer, 0.1 to 1 parts of antioxidant, 1 to 3 parts of lubricant, 5 to 30 parts of modified inorganic filler and 1 to 5 parts of ultraviolet radiation auxiliary agent.

2. A low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film, characterized in that: The invention is prepared from the following raw materials in parts by weight: 15-25 parts of polylactic acid resin, 80-90 parts of polybutylene terephthalate adipate resin, 0.5-3 parts of chain extender and compatibilizer, 0.1-1 parts of antioxidant, 1-3 parts of lubricant, 8-25 parts of modified inorganic filler and 1-5 parts of ultraviolet radiation auxiliary agent.

3. The low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film according to claim 1, characterized in that: The capacity-increasing and chain-extending agent is one or two of ADR4370S, ADR4370F, ADR4368, ADR4468, ADR4400, and SG-20.

4. The low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film according to claim 1, characterized in that: The antioxidant is at least one of phenolic antioxidants, vitamin E, thioester antioxidants, and phosphite antioxidants.

5. The low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film according to claim 1, characterized in that: The lubricant is one of stearic acid lubricants, acrylate lubricants, polyethylene wax powder, and silicone.

6. The low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film according to claim 1, characterized in that: The modified filler is at least one of nano calcium carbonate, nano silicon dioxide, organic modified montmorillonite, talcum powder, diatomaceous earth, nano hydroxyapatite (n-HA), and microcrystalline cellulose, and the filler size is 100nm-50μm.

7. The low-cost, high-performance, fully biodegradable polylactic acid-based heat shrinkable film according to claim 1, characterized in that: The ultraviolet irradiation auxiliary agent is one or two of benzophenone, methyl benzoylformate, alkyl phenones, triallyl isocyanurate, benzoin dimethyl ether, 1-hydroxycyclohexyl phenyl ketone and benzil.

8. A method for preparing a low-cost, high-performance, fully biodegradable polylactic acid-based heat-shrinkable film according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, after premixing the raw materials evenly and removing impurities, enter the extruder, extrude to obtain a heat shrinkable film sheet, wherein the premixing speed is 250-400rpm, the premixing time is 3-5min; the extrusion section temperature of the extruder is 170-190°C, the die temperature is 200-220°C, the twin screw speed is 60-100rpm; the thickness of the extruded sheet of the extruder is 300-800μm; S2, the plasticized heat shrinkable film sheet is expanded, stretched and cooled by compressed air at the die to obtain a heat shrinkable film semi-finished product; wherein the compressed air pressure in the film blowing section is 0.6-0.8 MPa; the film stretching rate is set to 150-300 mm / min; S3, the semi-finished heat-shrinkable film formed by expansion and stretching is irradiated and cross-linked by an ultraviolet curing machine to obtain a heat-shrinkable film; wherein the power of the ultraviolet curing machine is 80-120W / cm; the film passing rate is set to 150-300mm / min; the wavelength range of the ultraviolet light used is 300-450nm; S4, inspect the heat shrink film and cut it.

9. The method for preparing a low-cost, high-performance, fully biodegradable polylactic acid-based heat-shrinkable film according to claim 8, characterized in that: The thickness of the heat shrinkable film in S3 is 20-30 μm.

Citation Information

Patent Citations

  • A high barrier biodegradable composite film and its preparation process

    CN115593061B

  • Modified master batch of full-biodegradable thermal shrinkage film and preparation method of modified master batch

    CN117304666A

Cited By

  • Preparation method and application of dynamically crosslinked PLA / PBS material

    CN121045772A